2020
DOI: 10.3390/app10031054
|View full text |Cite
|
Sign up to set email alerts
|

Compression Shear Properties of Bonded–Bolted Hybrid Single-Lap Joints of C/C Composites at High Temperature

Abstract: Based on previous research, in this paper, the compressive shear failure behavior and mechanical properties of bonded–bolted hybrid single-lap joints of C/C composites at high temperature were studied. The compression shear test was performed on the joints at 800 °C to obtain the load–displacement curve and failure morphology. The failure modes of joints were observed by digital microscopy and scanning electron microscopy. A numerical analysis model was implemented in finite element code Abaqus/Explicit embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is due to the excellent thermal stability and resistance to degradation of polyurethane materials. Kwiecie ń et al [29] confirmed resistance of a single polyurethane material (used in this study in research) against various ageing factors, showing also that it presents stable properties in elevated temperatures up to 200 • C. However, it is critical to understand the limits and potential damage modes of polyurethane joints in wood buildings under different temperature conditions [30,31].…”
Section: Introductionmentioning
confidence: 52%
“…This is due to the excellent thermal stability and resistance to degradation of polyurethane materials. Kwiecie ń et al [29] confirmed resistance of a single polyurethane material (used in this study in research) against various ageing factors, showing also that it presents stable properties in elevated temperatures up to 200 • C. However, it is critical to understand the limits and potential damage modes of polyurethane joints in wood buildings under different temperature conditions [30,31].…”
Section: Introductionmentioning
confidence: 52%
“…As related to applied clamping torque, bolt heads, and washers compress the adhesive layer. This pressure transferred to the adhesive layer can increase joint strength by slowing the crack spread during loading 46 . In addition, fiber‐tearing is not observed as clamping pressure also limits the formation of interlaminar delaminations within the adherend.…”
Section: Resultsmentioning
confidence: 99%
“…This pressure transferred to the adhesive layer can increase joint strength by slowing the crack spread during loading. 46 In addition, fiber-tearing is not observed as clamping pressure also limits the formation of interlaminar delaminations within the adherend. As a result of these phenomena, which allow the load to concentrate into the adhesive, the deformation of the adhesive increases, and cohesion failure is more common.…”
Section: Evaluation Of Joint Performances For Different Fiber Reinfor...mentioning
confidence: 99%
“…Such failure traits as the chief damage patterns and fiber cracks of the samples were investigated. In the literature, experimental, analytical, and numerical modeling techniques have been used to explore damage mechanisms in composites [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%